2017
DOI: 10.1371/journal.pone.0187415
|View full text |Cite
|
Sign up to set email alerts
|

A chimeric IgE that mimics IgE from patients allergic to acid-hydrolyzed wheat proteins is a novel tool for in vitro allergenicity assessment of functionalized glutens

Abstract: BackgroundAcid-hydrolyzed wheat proteins (acid-HWPs) have been shown to provoke severe allergic reactions in Europe and Japan that are distinct from classical wheat allergies. Acid-HWPs were shown to contain neo-epitopes induced by the deamidation of gluten proteins. However, products with variable rates of deamidation can be found.ObjectivesIn this work, we studied the effect of the extent of wheat proteins deamidation on its allergenicity. A recombinant chimeric IgE was produced and compared to patients’ IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This was also the case of mAbs generated to Art v 3, which showed good overlap with patient IgE 41 . This sub-group of anti-Nat-LTP mAbs could enable generation of recombinant monoclonal IgE as substitutes mimicking patients reactivity 49 .…”
Section: Discussionmentioning
confidence: 99%
“…This was also the case of mAbs generated to Art v 3, which showed good overlap with patient IgE 41 . This sub-group of anti-Nat-LTP mAbs could enable generation of recombinant monoclonal IgE as substitutes mimicking patients reactivity 49 .…”
Section: Discussionmentioning
confidence: 99%
“…HWPs, derived from gluten through chemical or enzymatic partial hydrolysis, exhibit increased solubility, as well as enhanced foaming and emulsifying abilities, making them frequently used in cosmetic products and foods [35]. Their functional properties and molecular composition vary depending on the treatment method [35,36], and hydrolysis may reveal or create new allergenic epitopes or influence allergen absorption [18,37,38]. HWPs in cosmetics are recognized as a potential cause of percutaneous sensitization leading to WALDA [19,37,39].…”
Section: Discussionmentioning
confidence: 99%
“…This product contained large sized proteins (40-50 kDa). Unfortunately, this product caused anaphylactic sensitization to wheat in a large number (>1000) of Japanese people (Chinuki & Morita, 2012;Chinuki et al, 2013;Fukutomi et al, 2011;Nakamura et al, 2013;Noguchi et al, 2019;Tranquet et al, 2017;Yokooji et al, 2013). An expert committee that reviewed the allergenicity of HWP and HWG concluded that these products are safe only when they are formulated to minimize peptide lengths greater than 30 amino acids (∼3.3 kDa; Burnett et al, 2018).…”
Section: Industrial Processing Can Be Used To Produce Hypo-/nonallergenic Hydrolyzed Wheat Productsmentioning
confidence: 99%